Quantitative trait loci for cuticular hydrocarbons associated with sexual isolation between Drosophila simulans and D. sechellia. - Gleason, J.M.; Jallon, J.M.; Rouault, J.D.; Ritchie, M.G. (Genetics, 2005)
The identification of genes with large effects on sexual isolation and speciation is an important link between classic evolutionary genetics and molecular biology. Few genes that affect sexual isolation and speciation have been identified, perhaps because many traits influencing sexual isolation are complex behaviors. Cuticular hydrocarbons (CHs) of species of the Drosophila melanogaster group play a large role in sexual isolation by functioning as contact pheromones influencing mate recognition. Some of the genes that play key roles in determining species-specific CHs have been identified. We have performed separate quantitative trait locus (QTL) analyses of 7-tricosene (7-T) and 7,11-heptacosadiene (7,11-HD), the two major female CHs differing between D. simulans and D. sechellia. We find that approximately 40% of the phenotypic variance in each CH is associated with two to four chromosomal regions. A region on the right arm of chromosome 3 contains QTL that affect both traits, but other QTL are in distinct chromosomal regions. Epistatic interactions were detected between two pairs of QTL for 7,11-HD such that if either were homozygous for the D. simulans allele, the fly was similar to D. simulans in phenotype, with a low level of 7,11-HD. We discuss the location of these regions with regard to candidate genes for CH production, including those for desaturases.